CSIG-01. EGFR AND AXL RECEPTOR TYROSINE KINASES DRIVE ONCOGENESIS BY LZTR1 MUTATION. (14th November 2022) - Ko, Aram; Hasanain, Mohammad; Oh, Young Taek; D'Angelo, Fulvio; Sommer, Danika; Frangaj, Brulinda; Tran, Suzanne; Bielle, Franck; Pollo, Bianca; Paterra, Rosina; Mokhtari, Karima; Soni, Rajesh; et al.
Abstract: LZTR1, the substrate-specific adaptor of a CUL3-dependent ubiquitin ligase is among the most frequently mutated ubiquitin ligase coding gene in syndromic and sporadic human cancers including glioblastoma multiforme, in which approximately 27% of cases harbor inactivating mutations and copy number loss. However, both the identity of the protein substrates targeted by LZTR1-mediated ubiquitylation and the biological contexts regulated by specific LZTR1-substrate(s) interactions remain uncertain. Here, we combined biochemical and genetic studies to identify LZTR1 substrates and interrogated their tumor-driving function in the context of LZTR1 loss-of-function mutations and in a new conditional Lztr1 knockout mouse. Multiple screens converged on the receptor tyrosine kinases EGFR and AXL as LZTR1 interactors targeted for ubiquitin-dependent degradation in the lysosome by LZTR1-CUL3 complexes. Pathogenic mutations affecting LZTR1 failed to promote degradation of EGFR and AXL in human tumors. Mice harboring conditional deletion of the LZTR1 gene combined with loss of CDKN2A in the neural progenitor compartment generated peripheral nervous system tumors including schwannoma like and malignant peripheral nervous system tumors (MPNST). Tumors from the LZTR1 -mutant mouse model accumulated very high levels of EGFR and AXL and exhibited potent and specific vulnerability to the combinatorial inhibition of EGFR and AXL kinases. These findings explain the mechanism of tumorigenesis associated with LZTR1 inactivation and offer a therapeutic strategy to patients affected by tumors carrying mutations of LZTR1 .